2022
DOI: 10.1146/annurev-cellbio-120420-020656
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Ciliate Biology

Abstract: Ciliates are a diverse group of unicellular eukaryotes that vary widely in size, shape, body plan, and ecological niche. Here, we review recent research advances achieved with ciliate models. Studies on patterning and regeneration have been revived in the giant ciliate Stentor, facilitated by modern omics methods. Cryo-electron microscopy and tomography have revolutionized the structural study of complex macromolecules such as telomerase, ribozymes, and axonemes. DNA elimination, gene scrambling, and mating ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 180 publications
0
5
0
Order By: Relevance
“…Returning briefly to the behavior of the P. bursaria with and without Chlorella endosymbionts, we see that the cells' reaction of an AR and an action potential, which is to a step up in light and transient depolarization, keeps these cells in the shade by a klino-kinesis mechanism [41]. Likewise, when cells with Chlorella experience a step down to lower light, they have an AR that can send them back into the lighted area.…”
Section: Neuronal Properties Of Ciliamentioning
confidence: 90%
See 2 more Smart Citations
“…Returning briefly to the behavior of the P. bursaria with and without Chlorella endosymbionts, we see that the cells' reaction of an AR and an action potential, which is to a step up in light and transient depolarization, keeps these cells in the shade by a klino-kinesis mechanism [41]. Likewise, when cells with Chlorella experience a step down to lower light, they have an AR that can send them back into the lighted area.…”
Section: Neuronal Properties Of Ciliamentioning
confidence: 90%
“…These P. bursaria can be studied with or without the Chlorella, setting up an interesting comparison and control. Iwatsuki and Naitoh [41] showed that P. bursaria are intrinsically photosensitive, even without symbionts like Chorella that are photosynthetic. They point out that Chlorella symbionts alter the intrinsic responses of P. bursaria to changes in light; Without Chlorella, P. bursaria react to the step up in light with an avoiding reaction (AR) and transient depolarization, which help to keep the cells in the shade and out of harmful radiation.…”
Section: Endosymbiontsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciliates, including Tetrahymena and Paramecium, are powerful unicellular model organisms that have been used to uncover fundamental insights in diverse biological processes from DNA replication to the microtubule cytoskeleton [1][2][3] . Recently, the ciliate Stentor coeruleus has received renewed interest as a model for studying wound healing, regeneration, habituation and learning in a unicellular system [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Ciliates, including Tetrahymena and Paramecium , are powerful unicellular model organisms that have been used to uncover fundamental insights in diverse biological processes from DNA replication to the microtubule cytoskeleton 1 3 . Recently, the ciliate Stentor coeruleus has received renewed interest as a model for studying wound healing, regeneration, habituation and learning in a unicellular system 4 7 .…”
Section: Introductionmentioning
confidence: 99%